International teacher education promising pedagogies (part A) - Orland-Barak, Lily.; Craig, Cheryl J. (Bingley, U.K. : Emerald, 2014)
To this point in time, teacher education has been approached in mostly insular ways because it is largely driven by state and national education policies. However, the spread of the global economy and the increased stature of international comparison tests (i.e., TIMSS) has changed all that. All countries in the world understand that education is vital to human and economic prosperity and that teacher education unavoidably is implicated. But the snag is this: political forces shaping public opinion in individual nations (particularly the U.S.) are deeply divided concerning how teacher education should proceed. This book acknowledges this Achilles heel tension, but does not become weighed down by it. Instead, it focuses on 'the practical' (Schwab, 1969), matters that have been locally deliberated and enacted. Pedagogies are named, origins (cultural/practical/theoretical/policy roots) are traced and a live example of the pedagogy unfurling in the local setting is presented from an insider-view. After that, the conditions necessary for the pedagogy to be transported successfully to another international location are discussed.
International teacher education : promising pedagogies introduction / Lily Orland-Barak, Cheryl J. Craig -- Pedagogies of teacher selection : a South Korean case / JeongAe You -- Pedagogies of teacher preparation : the case of mathematics enhancement courses in England / John Clarke, Jean Murray -- One teacher educator's career-long development of a pedagogy of reflection / Tom Russell -- Promoting core reflection in teacher education : deepening professional growth / Fred A.J. Korthagen -- Reflection and work context in teacher learning : two case studies from Iceland / Hafdís Ingvarsdóttir -- Pedagogies of reflection : dialogical professional-development schools in Israel / Arie Kizel -- Self-study of teacher education practices as a pedagogy for teacher educator professional development / Mary Lynn Hamilton , Stefinee Pinnegar -- Narrative pedagogies for peer groups / Eila Estola, Hannu L.T. Heikkinen, Leena Syrjälä -- Dispersed narratives and powerful teacher education pedagogy / Amanda McGraw -- The narrative as the practical and the practice : towards the preparation of teachers / Jason Loh -- Narrative teacher education pedagogies from across the Pacific / Edward Howe, Masahiro Arimoto -- Literacy narratives for 21st century curriculum making : the 3Rs to excavate diverse issues in education / Darlene Ciuffetelli Parker -- Pedagogies of developing teacher identity / John Loughran -- Narrative-biographical pedagogies in teacher education / Geert Kelchtermans -- Pedagogies of developing teacher identity / Paulien C. Meijer ... [et al.] -- Pedagogies of developing teacher identity / Ali Leijen, Katrin Kullasepp, Tiina Anspal -- Teacher as researcher : an epistemic pedagogy for reconstructing teacher professional identity in Iran / Khalil Gholami, Mahmoud Mehrmohammadi -- Developing teacher identity in preservice education : experiences and practices from Portugal / Maria Assunção Flores -- Collaborative mentoring pedagogy in initial teacher education : lessons from a Scottish context / Semiyu Adejare Aderibigbe -- Mentoring and mediating the interface of multiple knowledges in learning to teach challenging content / Steven Z. Athanases -- Using action research to foster preservice teachers' reflection on themselves as learners : examining beliefs and changing practices / Carmen Montecinos, Andrea Ceardi, M. Beatriz Fernández -- International teacher education : promising pedagogies concluding chapter / Cheryl J. Craig, Lily Orland-Barak.
Print version record
Keywords: Education -- Teaching Methods & Materials -- General; Education -- Research; Education -- General; Teaching skills & techniques; Education; Teachers -- Training of -- Cross-cultural studies